Post extraction inversion slice imaging for 3D velocity map imaging experiments. (17th January 2021) - Allum, Felix; Mason, Robert; Burt, Michael; Slater, Craig S.; Squires, Eleanor; Winter, Benjamin; Brouard, Mark
ABSTRACT: An experimental configuration for velocity map ion imaging experiments is presented, in which a pulsed voltage defocusses the ion Newton sphere along the time-of-flight axis. This significantly spreads the times-of-flight for ions with the same mass-to-charge ratio, allowing for either sliced or three-dimensional velocity imaging with high slicing resolution along the time-of-flight axis. The technique is coupled to an event-triggered, position-sensitive sensor, enabling full three-dimensional Newton sphere imaging at high count rates, with significantly improved slicing resolution (∼1–2%) compared to previous DC slicing approaches. Good slice imaging conditions can be brought about at relatively high extraction voltages, circumventing issues regarding image size, stray fields, and poor detection efficiency when operating at low extraction voltages. The method, termed Post Extraction Inversion Slice Imaging (PEISI) was optimised through ion trajectory simulations and experimentally verified on the well-studied photodissociation of OCS at around 230 nm. We demonstrate that this approach is suitable for recording full 3D angular distributions of systems lacking an axis of cylindrical symmetry in the detector plane, where conventional image inversion techniques are invalid. This method could be useful in a range of systems lacking cylindrical symmetry, including studies into angular momentum polarisation and bimolecular scattering. GRAPHICAL ABSTRACT: